Culturally Relevant Pedagogies in Enhancing Students Learning of ICT Concepts: A Test of the Efficacy of CTCA - Oladejo, Adekunle I.; Akinola, Victor O.; Ebisin, Aderonke F.; Olateju, Taibat T. (West African Journal of Open and Flexible Learning, 2022)
The study is concerned with the persistent underperformance of secondary school students in Nigeria in Information and Communication Technology (ICT). It was conducted in response to the ever-growing call on culturally relevant and contextually responsive pedagogies in African classrooms. A quasi-experimental research design was adopted with a total of 217 SS2 students from two schools in Lagos State education district V. The control group, taught with the lecture method, had 112 subjects (64 males; 51 females) while the experimental group, taught with Culturo-Techno- Contextual Approach (CTCA), had 105 subjects (49 males; 56 females). Both groups had a pretest and a retention test using the achievement test in the programme development circle (PDC) instrument. Treatment lasted four weeks. The data collected was analysed using one-way ANCOVA since intact classes were used. The result obtained showed that the experimental group performed better (mean for experimental = 20.31; control 15.54; [F(1,214)=103.96; p
Keywords: ICT; Culturally relevant pedagogy; Culturo-Techno- Contextual Approach; Meaningful learning